EVALUATION OF THE QUALITY OF PHYSICS EDUCATION LABORATORY SERVICES BASED ON THE CIPP AND SERVQUAL MODELS - Afrida, Juniar; Zahriah, Zahriah; Fahira, Adinda (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This research intends to scrutinize the quality of service program at the Physics Education Laboratory, Faculty of Tarbiyah and Teacher Training UIN Ar-Raniry Banda Aceh by employing a double CIPP-SERVQUAL integrated framework in which it merged adopted frameworks to source out comprehensive points from both managerial and user views. A mixed method design including questionnaires, observations, interviews and document analysis of students, lecturers, laboratory assistants and laboratory coordinators was used. The assessment included the Context, Input, Process and Product of the CIPP model combined with six SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance and empathy as well as information systems. The outcomes showed that the Context, Process and Product modules were “Very Good,” reflecting internal consistency between laboratory services and academic demand, rational operation management and impacts on student competences, particularly in comprehensive application and experimental manipulation. The Input element was “Good” indicating constraints due to manual documentation and resource upgrade. The originality of this research is to combine the CIPP and SERVQUAL models in order to simultaneously measure than the Internal management efficiency, the perceived quality of service from user point of view in a physics education laboratory. The results suggest that improving digital documentation systems, preventive maintenance and technical response is an important strategy to increase the quality level of laboratory services, allowing support for sustainable learning in higher education.